P Pengaruh Shared Leadership Terhadap Job Crafting Melalui Learning Goal Orientation dan Knowledge Sharing Pada Karyawan RSI Jemursari Surabaya - Niken Nurul Nurhidayah (Jurnal Ilmu Manajemen, 2022)
This study aims to identify and explain the effect of shared leadership on job crafting through learning goal orientation and knowledge sharing for employees of RSI Jemursari Surabaya. This research is a quantitative study using statistical analysis of Partial Least Square (PLS) with the help of SmartPLS 3.0 software. This study used 99 samples with purposive sampling technique. The results of this study explain that shared leadership has a significant effect on job crafting. Shared leadership has an influence on learning goal orientation. Shared leadership has an influence on knowledge sharing. Learning goal orientation has a significant influence on job crafting. Knowledge sharing has an effect on job crafting. Learning goal orientation has a significant influence on knowledge sharing. The role of the mediator of learning goal orientation and knowledge sharing has a significant effect between shared leadership and job crafting. Companies need to provide environmental conditions that encourage employees to improve their competence and proactive behavior, encourage them to set clear and specific goals through shared leadership and support employees to be part of the collective desicion making process by creating a horizontal sctructure.